Extraction and identification of trophoblast cells circulating in peripheral blood during pregnancy - Goodfellow, C F; Taylor, P V (British journal of obstetrics and gynaecology, 1982)
Trophoblast cells circulating in peripheral venous blood during pregnancy were extracted by differential centrifugation and identified by indirect immunofluorescence with antitrophoblast microvillus antibody. In a study where trophoblast identification was checked by blind comparison with non-pregnant control subjects' trophoblast cells were detected in six out of 10 pregnant women studied.